Characteristics of diabetic nephropathy patients without diabetic retinopathy: A retrospective observational study. Issue 18 (May 2017) - Li, Xiao-Qian; Zheng, Xin; Chen, Min; Zhao, Ming-Hui
Abstract : Abstract: The purpose of the current study was to investigate the characteristics of patients with diabetic nephropathy (DN) without diabetic retinopathy (DR). One hundred four patients with biopsy-proven DN, and 52 patients with diabetes mellitus (DM) without DR who were diagnosed as membranous nephropathy by renal biopsy were retrospectively included. We compared the clinical and laboratory parameters of DN patients with and without DR. Furthermore, among the DM patients without DR, we compared those with DN and with membranous nephropathy. Among patients with DN, including those with pure DN and DN coexisting with nondiabetic renal disease, compared with patients with DR, those without DR had significantly higher levels of serum albumin and hemoglobin (31.72 ± 7.97 vs 28.49 ± 6.30 g/L, P  = .023; 128.11 ± 21.87 vs 113.06 ± 22.03 g/L, P  = .001, respectively), and significantly lower level of serum creatinine and prevalence of diabetic neuropathy (148.56 ± 99.19 vs 203.75 ± 145.36 μmol/L, P  = .028; 7.30% vs 32.70%, P  = .001, respectively). Among patients with pure DN, compared with patients with DR, those without DR had significantly higher level of serum albumin (33.91 ± 5.79 vs 29.32 ± 5.42 g/L, P  = .012). Among DM patients without DR, patients with membranous nephropathy had significantly lower levels of serum albumin and serum creatinine, and significantly higher levels of high-density lipoprotein and cholesterol than those with DN. In conclusion, DN patients without DR may have less serious renal damage and less diabetic complication than those with DR. In the absence of DR, there is still a lack of effective indicators suggesting diabetic nephropathy or nondiabetic glomerulopathy, and renal biopsy is indispensable for diagnosis in such circumstances.